Planisphere physique, où l'on voit du Pole Septentrional ce que l'on connoit de terres et de mers : avec les grandes chaines de montagnes qui traversent le globe - Bauche, Philippe, 1700-1773; Schenk Jansz, Leonard, 1732-1800 (l'Academie [Rle. Des Sc.], 1752)
This map shows the world as a physical planisphere projection, as viewed from the North Pole. Some geographic features are marked (with relief shown by hachures). Prime meridian: Isle de Fer.